An HPLC-UV method for the quantification of zidovudine in rat plasma - Carvalho, Flávia Chiva [UNESP]; Campos, Michel Leandro [UNESP]; Peccinini, Rosangela Goncalves [UNESP]; Gremião, Maria Palmira Daflon [UNESP] (Elsevier, 2013)
This work aims to develop and validate a simple methodology to quantify the most used antiretroviral, zidovudine (AZT), in rat plasma for preclinical studies. Some assays have been previously reported to quantify AZT in plasma; however, the majority of these methods uses complicated extraction methods. This method uses only 100 μL plasma samples, which were precipitated with 100 μL acidified acetonitrile containing an internal standard (IS). The plasma extracts were injected directly in a chromatographic system consisting of a UV-Vis detector (set at 266 nm) and an RP-C18 column. The mobile phase was an isocratic mixture of acetonitrile, methanol and 0.01% v/v aqueous formic acid (20:20:60 v/v/v) at a flow rate of 0.8 mL/min. Intra- and inter-day assay precision and accuracy variability were lower than 20% for the limit of quantification and 15% for higher concentrations. The applicability of the method was demonstrated by an in vivo study performed in rats. They were treated orally with an AZT-containing syrup and intravenously with an AZT solution. The calculated bioavailability of the syrup (56.7%) was in accordance with the literature. Therefore, this method can be used as an alternative to quantify plasma AZT in preclinical studies. © 2013 Bentham Science Publishers.
Keywords: HPLC-UV bioanalytical methodology; Liquid-liquid extraction; Pharmacokinetics; Rat plasma; Validation; Zidovudine; acetonitrile; formic acid; methanol; zidovudine; accuracy; animal experiment; assay; bioavailability; drug absorption; drug blood level; drug distribution; extraction; flow rate; high performance liquid chromatography; in vivo study; liquid liquid extraction; male; medical device; methodology; nonhuman; plasma; priority journal; rat; standard; syrup